Pengaruh Kombinasi Minyak Jelantah Dan Asam Stearat Pada Sediaan Lilin Aromaterapi Kopi Arabika (Coffea arabica) - Anggraini, Cristine; Kurniasih, Trifonia Rosa (Jurnal Farmasi & Sains Indonesia, 2024)
Waste cooking oil is cooking oil that has been used repeatedly. Indiscriminate disposal of used cooking oil has the potential to pollute soil and water. If used cooking oil is not managed properly, it can seep into the soil and cause the soil to become infertile. Efforts can be made to reduce the negative impact of used cooking oil by converting used cooking oil into raw materials for making aromatherapy candles. This study aims to utilize waste cooking oil as a base material for making candles with arabica coffee aroma and to obtain a formula that has good physical evaluation results. This type of research is pure experiment. This research was conducted by making three formulas with different ratios of used cooking oil and stearic acid, namely formula I (1:1), formula II (1:4) and formula III (3:5). Data were not normally distributed (α<0.05) so it was continued using the Kruskal-Wallis test to compare between groups with 95% confidence level. Based on the evaluation of physical properties, namely organoleptic test, melting point test and burn time test, formula III showed good physical properties compared to formula I and formula II. Formula III (3:5) produced solid candles, no cracks, homogeneous dark brown color, highest melting point 55.33 ± 0.33 SE, longest burning time 253.45 ± 8.13 compared to formula I and II. The combination of waste cooking oil and stearic acid has a significant effect on burn time. Overall, the aromatherapy candle preparations produced have meets the SNI criteria for candle preparations.